CHANGES IN PHYSIOLOGICAL PARAMETERS IN CADET WRESTLERS FOLLOWING A 4-WEEK GENERAL PREPARATION PHASE - Bahman Mirzaei; Farhad Rahmani-Nia; David G. Curby; Ioanis Barbas; Navid Lotfi (Fizičeskoe Vospitanie Studentov, 2011)
The purpose of this study was to investigate the changes in physiological parameters in cadet wrestlers following a 4-week general preparation phase of training. The physiological parameters included cardiovascular endurance, muscular endurance, speed, agility, flexibility, anaerobic power and body composition. In experiment took part 15 cadet wrestles at the age of 15 years. The testing was conducted twice, before and after the 4-week training period.